Impact of Anaerobiosis on Expression of the Iron-Responsive Fur and RyhB Regulons - Beauchene, Nicole A. (mBio, 2015)
Iron, a major protein cofactor, is essential for most organisms. Despite the well-known effects of O(2) on the oxidation state and solubility of iron, the impact of O(2) on cellular iron homeostasis is not well understood. Here we report that in Escherichia coli K-12, the lack of O(2) dramatically changes expression of genes controlled by the global regulators of iron homeostasis, the transcription factor Fur and the small RNA RyhB. Using chromatin immunoprecipitation sequencing (ChIP-seq), we found anaerobic conditions promote Fur binding to more locations across the genome. However, by expression profiling, we discovered that the major effect of anaerobiosis was to increase the magnitude of Fur regulation, leading to increased expression of iron storage proteins and decreased expression of most iron uptake pathways and several Mn-binding proteins. This change in the pattern of gene expression also correlated with an unanticipated decrease in Mn in anaerobic cells. Changes in the genes posttranscriptionally regulated by RyhB under aerobic and anaerobic conditions could be attributed to O(2)-dependent changes in transcription of the target genes: aerobic RyhB targets were enriched in iron-containing proteins associated with aerobic energy metabolism, whereas anaerobic RyhB targets were enriched in iron-containing anaerobic respiratory functions. Overall, these studies showed that anaerobiosis has a larger impact on iron homeostasis than previously anticipated, both by expanding the number of direct Fur target genes and the magnitude of their regulation and by altering the expression of genes predicted to be posttranscriptionally regulated by the small RNA RyhB under iron-limiting conditions.